1998
DOI: 10.1021/la9712348
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Observation of Plasma Protein Film Formation on Well-Defined Surfaces with Scanning Force Microscopy

Abstract: We report here the results of a scanning force microscopic (SFM) investigation into the structure of adsorbed bovine fibrinogen films on well-defined surfaces. SFM images show that a monolayer of fibrinogen assembles on both highly oriented pyrolytic graphite (HOPG) and mica. We find, however, that the film morphology varies as a function of the substrate. To unravel the nature of the observed differences, we tracked the growth of bovine fibrinogen layers at both surfaces in real-time. Consistent with the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
115
1
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(136 citation statements)
references
References 56 publications
16
115
1
4
Order By: Relevance
“…Even if sheet formation in vivo is confined to the space very near surfaces, their formation could be a first step in clot formation at newly exposed subendothelial matrix after injury or dislodgment of a plaque, or on the surfaces of implanted vascular stents. AFM studies have shown that fibrinogen adheres to both hydrophobic and hydrophilic surfaces, but is oriented differently by each and is more strongly attracted to the former (40)(41)(42). In our study we see that fibrin sheets form and adhere to both hydrophobic polyurethane SSs, and relatively hydrophilic copper and glass.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Even if sheet formation in vivo is confined to the space very near surfaces, their formation could be a first step in clot formation at newly exposed subendothelial matrix after injury or dislodgment of a plaque, or on the surfaces of implanted vascular stents. AFM studies have shown that fibrinogen adheres to both hydrophobic and hydrophilic surfaces, but is oriented differently by each and is more strongly attracted to the former (40)(41)(42). In our study we see that fibrin sheets form and adhere to both hydrophobic polyurethane SSs, and relatively hydrophilic copper and glass.…”
Section: Discussionsupporting
confidence: 58%
“…2C) is larger than reported AFM measurements of individual fibrinogen monomers, with maximum values of 1 to 2 nm (40,41). However, those authors and others (42) have shown that imaging of individual fibrin molecules is strongly affected by surface attraction and imaging conditions, and heights so obtained tend to be underestimates relative to estimates by crystal structure. Within a sheet, each subunit is supported through multiple interactions with neighboring monomers, and thus would be less distorted by surface effects.…”
Section: Discussionmentioning
confidence: 66%
“…This can be attributed to the electrostatic force between the protein layer and the mica, which is repulsive, for they are both negatively charged at pH 7.4. 34 As the ionic strength is increased to 150 mM, the probe is no longer repelled from the surface, but it is attracted by it. The increase of the NaCl concentration results in the reduction of the thickness of the diffusive double layers in both the protein layer and the mica surface, 35 so that the electrostatic repulsion is restricted in range and the van FIG.…”
Section: B Force Profiles Upon Approach With Variation In Ionic Strementioning
confidence: 99%
“…Several authors 5,25 have suggested fibrinogen conformational changes at pH 3.5, with the C-terminal regions of the ␣ chains being detached from the central E domain of the molecule. These ␣C arms are positively charged 34,51 and, therefore, when they become free from the E domain, they may readily interact with the negatively charged mica surface. On the other hand, they may play a crucial role in fibrinogen polymerization into fibrin, since their detachment from the central domain possibly leaves the fibrinopeptides A and B uncovered.…”
Section: Influence Of Phmentioning
confidence: 99%
“…Observations of adsorption to mica were previously made by two other groups, Marchin and Berrie 26 and Ta et al 30 These groups concluded that the positively charged ␣C arms that extend off of the D domains of the fibrinogen molecule present a favorable site of attachment to the negatively charged mica surface. 26,30 The suggestion that the positively charged ␣C arms would act as an adsorption "pioneer" and bind to a negatively charged hydrophilic surface was put forth first by Feng and Andrade. 31 Therefore, in the case of mica, it seems that the electrostatic interactions dominate the adsorption phenomenon leading to completely irreversible adsorption.…”
mentioning
confidence: 98%